Epidemiology of facial clefting. Issue 6 (June 1985) - Owens, J R; Jones, J W; Harris, F
Abstract : An analysis was performed of patients with facial clefts notified between 1960 and 1982 to the Liverpool Congenital Malformations Registry. From 1960-82 there were 325 727 births in the area surveyed and 544 cases of facial clefting were notified. When 88 patients with recognised syndromes and multiple congenital anomalies were excluded, the overall prevalence of facial clefts alone was 1.4 per 1000 total births. This group was then classified further into 137 cases of cleft lip alone, 166 cases of cleft lip and palate, and 153 cases of cleft palate alone. The prevalence of these groups per 1000 total births is 0.42, 0.51, and 0.47 respectively. There were some fluctuations in annual prevalence with rises being observed in the mid and late 1960s and mid and late 1970s. There was a noticeable male predominance in the cleft lip and cleft lip and palate groups of 1.52:1 and 1.98:1 respectively, with a 1:1 ratio in the cleft palate group. There were no significant differences in birthweight and mean maternal age in the three groups. In the cleft palate group, however, there was a significant trend towards an increase in the frequence of conception in the second half of the year. There was a maternal history of epilepsy in 4.4% of the cleft lip and 3% of the cleft lip and palate groups but only in 1 patient (0.6%) in the cleft palate group. The study illustrates the importance of environmental factors in the aetiology of facial clefting.